Pengaruh Latihan Passing dengan Pola Target untuk Meninggkatkan Akurasi Passing dalam Permainan Futsal di Sekolah Dasar - Muhammad Raghib Mahdi; Rizal Ahmad Fauzi; Adang Sudrazat (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine the effect of target pattern passing training on improving elementary school students' futsal passing ability. The research method used was an experiment with a One Group Pretest-Posttest Design. The research sample consisted of 10 students of SDN Hambalang 5, Bogor Regency. The research instrument used a low ball passing skill test. Data analysis techniques used descriptive statistics, normality tests, and paired sample t-tests. The results showed that the average pretest score of 3.50 increased to 6.60 in the posttest. The results of the paired sample t-test showed a significance value of 0.000 <0.05, which means there is a significant effect of target pattern passing training on students' passing ability. Thus, it can be concluded that target pattern passing training is effective in improving elementary school students' futsal passing ability. The novelty of this research lies in the application of a passing training model that is simple, structured, and appropriate to the characteristics of early childhood students. Keyword: Futsal, Training, Passing, Target Pattern, Elementary School Students